Artistic revisions in the works of Vladimir Nabokov - Miller, Lyndsay (2015)
Vladimir Nabokov, throughout a literary career spanning six decades, five countries, three languages, two continents and two calendars, was an inveterate reviser, constantly changing, translating and altering his own works. Indeed, Nabokov himself acknowledged that ‘even the dream I describe to my wife across the breakfast table is only a first draft’ (SO, xv). The very process of writing was, for Nabokov, inextricably linked with the act of revision. In his memoirs, for example, Nabokov compares his father’s handwritten texts, which were produced in ‘slanted, beautifully sleek, unbelievably regular hand, almost free of corrections’, against his ‘own mousy hand and messy drafts […] the massacrous revisions and rewritings, and new revisions, of the very lines in which I am taking two hours to describe a two-minute run of his flawless handwriting’ (SM, 139). This thesis will examine the deliberate, visible revisions, which Nabokov leaves purposefully within his fiction. The first category of revision, developmental revision, represents the evolutionary arc of central thematic matter within the author’s work. Secondly, fictional revisions are those implemented within the individual narratives of Nabokov’s texts, which are assigned as the work of Nabokov’s author-characters. Transtextual revision is carried out across texts and languages, creating links between individual works. Finally, extratextual revision, which is implemented to the individual text from an external vantage point, leads to the destabilisation of these texts as a result of Nabokov’s authorial intrusions. Taken together, these deliberately visible revisions destabilise the autonomy of texts, causing them to become incomplete. This results in a cohesive, self-reflexive oeuvre, within which all component parts can be seen together. This results in a dynamic model of oeuvre construction, which leads to the formation of what will be termed a ‘supertext’, that is a fully connected oeuvre, which has only its own self as reference.